At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's start by simplifying the given expression step by step:
[tex]\[ \frac{(2 g^5)^3}{(4 h^2)^3} \][/tex]
1. Simplify the numerator [tex]\((2 g^5)^3\)[/tex]:
To simplify [tex]\((2 g^5)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (2 g^5)^3 = 2^3 \cdot (g^5)^3 \][/tex]
Calculate each part:
[tex]\[ 2^3 = 8 \][/tex]
[tex]\[ (g^5)^3 = g^{5 \cdot 3} = g^{15} \][/tex]
Therefore,
[tex]\[ (2 g^5)^3 = 8 g^{15} \][/tex]
2. Simplify the denominator [tex]\((4 h^2)^3\)[/tex]:
To simplify [tex]\((4 h^2)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (4 h^2)^3 = 4^3 \cdot (h^2)^3 \][/tex]
Calculate each part:
[tex]\[ 4^3 = 64 \][/tex]
[tex]\[ (h^2)^3 = h^{2 \cdot 3} = h^6 \][/tex]
Therefore,
[tex]\[ (4 h^2)^3 = 64 h^6 \][/tex]
3. Combine the simplified numerator and denominator:
Now we can form the fraction with the simplified numerator and denominator:
[tex]\[ \frac{8 g^{15}}{64 h^6} \][/tex]
4. Simplify the fraction:
Divide the numerator and the denominator by their greatest common divisor, which is 8:
[tex]\[ \frac{8 g^{15}}{64 h^6} = \frac{8}{64} \cdot \frac{g^{15}}{h^6} = \frac{1}{8} \cdot \frac{g^{15}}{h^6} = \frac{g^{15}}{8 h^6} \][/tex]
Hence, the expression [tex]\(\frac{(2 g^5)^3}{(4 h^2)^3}\)[/tex] simplifies to:
[tex]\[ \frac{g^{15}}{8 h^6} \][/tex]
So, the equivalent expression is [tex]\(\boxed{\frac{g^{15}}{8 h^6}}\)[/tex].
[tex]\[ \frac{(2 g^5)^3}{(4 h^2)^3} \][/tex]
1. Simplify the numerator [tex]\((2 g^5)^3\)[/tex]:
To simplify [tex]\((2 g^5)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (2 g^5)^3 = 2^3 \cdot (g^5)^3 \][/tex]
Calculate each part:
[tex]\[ 2^3 = 8 \][/tex]
[tex]\[ (g^5)^3 = g^{5 \cdot 3} = g^{15} \][/tex]
Therefore,
[tex]\[ (2 g^5)^3 = 8 g^{15} \][/tex]
2. Simplify the denominator [tex]\((4 h^2)^3\)[/tex]:
To simplify [tex]\((4 h^2)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (4 h^2)^3 = 4^3 \cdot (h^2)^3 \][/tex]
Calculate each part:
[tex]\[ 4^3 = 64 \][/tex]
[tex]\[ (h^2)^3 = h^{2 \cdot 3} = h^6 \][/tex]
Therefore,
[tex]\[ (4 h^2)^3 = 64 h^6 \][/tex]
3. Combine the simplified numerator and denominator:
Now we can form the fraction with the simplified numerator and denominator:
[tex]\[ \frac{8 g^{15}}{64 h^6} \][/tex]
4. Simplify the fraction:
Divide the numerator and the denominator by their greatest common divisor, which is 8:
[tex]\[ \frac{8 g^{15}}{64 h^6} = \frac{8}{64} \cdot \frac{g^{15}}{h^6} = \frac{1}{8} \cdot \frac{g^{15}}{h^6} = \frac{g^{15}}{8 h^6} \][/tex]
Hence, the expression [tex]\(\frac{(2 g^5)^3}{(4 h^2)^3}\)[/tex] simplifies to:
[tex]\[ \frac{g^{15}}{8 h^6} \][/tex]
So, the equivalent expression is [tex]\(\boxed{\frac{g^{15}}{8 h^6}}\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.